Prepreg tape resin composition and carbon fiber prepreg
By optimizing the amount of components in the prepreg tape resin composition, the problem that prepreg tape resin in the prior art cannot take into account the curing temperature, storage period and toughness, and the performance improvement of carbon fiber-wrapped hydrogen storage IV bottle is achieved.
Patent Information
- Application Number
- CN202310801519.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the prepreg tape resin cannot take into account the low curing temperature, long shelf life, good toughness and good viscosity thixotropy, resulting in insufficient performance of carbon fiber-wrapped hydrogen storage IV bottles.
A prepreg tape resin composition, including bisphenol A type liquid epoxy resin, bisphenol A type solid epoxy resin, phenolic epoxy resin, core-shell nanoparticles, latent curing agent and accelerator, is adopted to optimize The dosage and combination of these ingredients produce resins that can cure at lower temperatures, have long shelf life and good toughness.
The prepreg tape resin is cured at medium temperature, extended shelf life, enhanced toughness and viscosity thixotropy, and achieved synergistic optimization, meeting the performance requirements of carbon fiber-wrapped hydrogen storage IV bottles.
Smart Images

Figure CN119220057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a prepreg tape resin composition and a carbon fiber prepreg material. Background Art
[0002] In order to cope with the increasingly severe oil crisis and environmental pollution problems, countries around the world have successively proposed carbon reduction targets and announced a timetable for the ban on the sale of fuel vehicles. Hydrogen fuel cell vehicles (FCVs) are known for being clean and pollution-free and are considered the ultimate energy source for vehicles. Therefore, countries have successively launched hydrogen fuel cell vehicles, and on-board hydrogen storage cylinders, as a bridge connecting hydrogen production and hydrogen use, play an irreplaceable role in the development of hydrogen fuel cell vehicles. In order to achieve higher hydrogen storage density, on-board hydrogen storage cylinders have been developing in the direction of lightweight and high storage pressure while ensuring safety. Today, carbon fiber wrapped hydrogen storage type IV bottles have become the mainstream development direction in the field of hydrogen storage for hydrogen fuel cell vehicles with their high hydrogen storage density, good fatigue resistance and higher storage pressure.
[0003] The structure of the carbon fiber wound hydrogen storage type IV bottle can be roughly divided into two layers. The inner layer is a plastic liner, which mainly plays the role of blocking hydrogen; the outer layer is a carbon fiber resin winding layer to ensure its strength in use, which is generally composed of carbon fiber and epoxy resin. The construction of the carbon fiber resin winding layer can be simply divided into two steps: one is to wind the continuous fiber impregnated with resin onto the liner through a winding process, and the other is to solidify it into shape through temperature or microwaves. There are currently two mainstream winding molding methods: one is wet winding molding, that is, the continuous carbon fiber is directly wound after being impregnated with glue; the other is dry winding molding, that is, the continuous carbon fiber is pre-impregnated with a certain amount of resin glue, and then refrigerated and stored, and taken out for winding when in use.
[0004] Compared with wet winding, dry winding has the advantages of controllable glue content, good process stability, stable molding, etc., and is suitable for mass production. The raw material for dry winding of hydrogen storage type IV bottles is prepreg tape, and the prepreg tape resin plays a decisive role in the performance of the prepreg tape. However, the prior art cannot make the prepreg tape resin have a low curing temperature, a long storage period, good toughness and good viscosity thixotropy at the same time. Therefore, it is necessary to provide a new prepreg tape resin to improve the above problems. Summary of the invention
[0005] The main purpose of the present invention is to provide a prepreg tape resin composition and a carbon fiber prepreg material to solve the problem that the prepreg tape resin in the prior art cannot simultaneously take into account a lower curing temperature, a longer storage period, better toughness and good viscosity thixotropy.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a prepreg resin composition is provided, which comprises, by weight: 25 to 80 parts of bisphenol A liquid epoxy resin, 20 to 75 parts of bisphenol A solid epoxy resin, 15 to 50 parts of phenolic epoxy resin, 5 to 20 parts of core-shell nanoparticles, 3 to 8 parts of latent curing agent, and 0.5 to 5 parts of accelerator; wherein the core of the core-shell nanoparticles is rubber and the shell is hard plastic.
[0007] Furthermore, the prepreg resin composition includes, by weight: 55-80 parts of bisphenol A liquid epoxy resin, 40-55 parts of bisphenol A solid epoxy resin, 15-40 parts of phenolic epoxy resin, 15-20 parts of core-shell nanoparticles, 4-6 parts of latent curing agent, and 1-3 parts of accelerator.
[0008] Furthermore, the particle size of the core-shell nanoparticles is 50 to 200 nm; preferably, in the core-shell nanoparticles, the hard plastic is selected from one or more of polymethyl methacrylate, polybutyl methacrylate or polystyrene; preferably, in the core-shell nanoparticles, the rubber is selected from one or more of silicone rubber, styrene-butadiene rubber or polybutadiene rubber; further preferably, the core-shell nanoparticles are selected from one or more of MX-154, MX-153, MX-960, XA-492 or XA-542.
[0009] Furthermore, the bisphenol A type liquid epoxy resin is selected from one or more of E-56D, E-54, E-52D, E-51, E-44B, E-44, E-42 or E-39D.
[0010] Furthermore, the bisphenol A type solid epoxy resin is selected from one or more of E-21, E-20, E-14, E-13, CYD-011, CYD-012 or CYD-001.
[0011] Further, the novolac epoxy resin is selected from one or more of linear phenol formaldehyde glycidyl ether, o-cresol formaldehyde glycidyl ether or resorcinol formaldehyde glycidyl ether; further preferably, linear phenol formaldehyde glycidyl ether is selected from one or more of F-51, F-48, F-44 or NPPN-638S; further preferably, o-cresol formaldehyde glycidyl ether is selected from one or more of JF-45, JF-46, JF-43 or EDCN-220; further preferably, resorcinol formaldehyde glycidyl ether is selected from F-76 and / or CYDPG-694.
[0012] Furthermore, the latent curing agent is selected from one or more of cyanamide compounds, imidazole derivatives or boron trifluoride complexes; preferably, the cyanamide compound is selected from dicyandiamide and / or diallylmelamine; preferably, the imidazole derivative is selected from 2MZ-AZINE and / or 2E4MZ-AZINE; preferably, the boron trifluoride complex is selected from BF3·MEA.
[0013] Further, the accelerator is selected from one or more of acetylacetonate metal salt accelerators, modified imidazole accelerators, modified urea accelerators, and modified tertiary amine accelerators; preferably, the acetylacetonate metal salt accelerator is selected from ferric acetylacetonate and / or chromium acetylacetonate; preferably, the modified imidazole accelerator is selected from 2,4-EMI and / or 2MZ-ZN; preferably, the modified urea accelerator is selected from DCMU and / or UR400; preferably, the modified tertiary amine is selected from one or more of MY-24, DMP-30 or TAP.
[0014] Further, the prepreg resin composition includes: E-54: 75-80 parts; CYD-011: 45-50 parts; JF-46: 15-20 parts; XA-542: 15-20 parts; BF3·MEA: 4-5 parts; 2,4-EMI: 0.5-1 parts; MY-24: 0.5-1 parts; or, the prepreg resin composition includes: E-44: 55-60 parts; CYD-001: 40-45 parts; F-48: 35-4 0 parts; MX-154: 15 to 20 parts; dicyandiamide: 5 to 6 parts; MY-24: 1 to 2 parts; DMP-30: 0.1 to 0.5 parts; or, the prepreg resin composition includes: E-51: 65 to 70 parts; CYD-012: 50 to 55 parts; F-51: 30 to 35 parts; XA-542: 15 to 20 parts; diallyl melamine: 5 to 6 parts; MY-24: 1 to 1.5 parts; 2,4-EMI: 1 to 1.5 parts.
[0015] In order to achieve the above object, according to one aspect of the present invention, a carbon fiber prepreg material is provided, the carbon fiber prepreg material comprising carbon fiber and the above prepreg tape resin composition impregnated in the carbon fiber
[0016] Based on the synergistic effect of the above-mentioned specific components and their dosages, the prepreg resin of the present application can simultaneously take into account lower curing temperature, longer storage period, better toughness and good viscosity thixotropy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 The viscosity-temperature curve of the prepreg resin composition in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] Bisphenol A type liquid epoxy resin: Bisphenol A type epoxy resin that is liquid at room temperature.
[0021] Bisphenol A type solid epoxy resin: Bisphenol A type epoxy resin that is solid at room temperature.
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The inventor proposes that the prepreg tape resin for the IV-type hydrogen storage bottle onboard hydrogen fuel cell vehicles must meet the following properties at the same time:
[0024] (1) Long storage period. In production, after the prepreg is impregnated, it is sometimes not put into production immediately. Therefore, the prepreg is required to have a long storage period and be able to be stored at room temperature for more than 30 days without curing.
[0025] (2) Lower curing temperature. The inner liner of the carbon fiber-wound hydrogen storage type IV bottle is mostly made of nylon or high-density polyethylene, which will undergo varying degrees of oxidation at 150-200°C, causing the inner liner to fail and performance to deteriorate. Excessively high curing temperatures can cause the plastic inner liner of the hydrogen storage type IV bottle to fail. Therefore, the curing temperature of the prepreg resin should not exceed 120°C, which can meet the medium-temperature curing requirements.
[0026] (3) Good viscosity thixotropy (i.e., it has a higher viscosity at low temperatures, and the viscosity drops rapidly after heating). In order for the prepreg resin to have good process stability, it is required to be solid or ultra-high viscosity liquid at room temperature to ensure that the prepreg resin does not drip after impregnation is completed and the yarn spreading is good. At the same time, in order to meet the requirements of the resin's wettability to carbon fiber during the impregnation process, the prepreg resin is required to be a low-viscosity liquid with a viscosity of 1000 to 5000 cps at 60 to 80°C; at the same time, the prepreg needs to be heated with a hot air gun during the winding process to make the glue flow. In order to ensure that the heating temperature does not damage the liner, the prepreg resin is also required to have good fluidity at 60 to 80°C.
[0027] However, as described in the background technology part of the present invention, the prepreg resin in the prior art cannot take into account lower curing temperature, longer storage period, better toughness and good viscosity thixotropy at the same time. In order to solve this problem, the present application provides a prepreg resin composition, which includes, by weight: 25 to 80 parts of bisphenol A liquid epoxy resin, 20 to 75 parts of bisphenol A solid epoxy resin, 15 to 50 parts of phenolic epoxy resin, 5 to 20 parts of core-shell nanoparticles, 3 to 8 parts of latent curing agent, and 0.5 to 5 parts of accelerator; wherein the core of the core-shell nanoparticles is rubber and the shell is hard plastic. Based on the synergistic effect of the above-mentioned specific components and their dosages, the prepreg resin of the present application can take into account lower curing temperature, longer storage period, better toughness and good viscosity thixotropy at the same time.
[0028] In order to optimize the carbon fiber impregnation effect of the prepreg in subsequent applications, the present application adds 25 to 80 parts of bisphenol A liquid epoxy resin to the prepreg resin composition. This amount of bisphenol A liquid epoxy resin gives the prepreg resin a certain fluidity, which can effectively improve the carbon fiber impregnation effect. Too low a content of bisphenol A liquid epoxy resin will result in a relatively high viscosity of the composition and a poor carbon fiber impregnation effect; while too high a content will result in a relatively soft composition, difficult to shape, and poor appearance. In order to optimize the storage period of the prepreg, the present application adds 3 to 8 parts of a latent curing agent as a curing agent component to the prepreg resin composition. However, the inventors found that the curing temperature of the latent curing agent is usually relatively high (between 160 and 200°C), and too high a curing temperature will cause the plastic liner of the hydrogen storage IV bottle to fail. In order to optimize the curing temperature of the prepreg, the present application further adds 0.5 to 5 parts of an accelerator to the composition to reduce the curing temperature of the prepreg resin, which can meet the medium temperature (not exceeding 120°C) curing. However, the inventors have found that the addition of accelerators will lead to a decrease in the toughness of the prepreg tape resin. In order to optimize the toughness of the prepreg tape, the present application further adds 5 to 20 parts of core-shell nanoparticles in the composition, wherein the core is rubber and the shell is hard plastic. Such core-shell nanoparticles can effectively improve the toughness of the prepreg tape resin.
[0029] At the same time, the room temperature viscosity of conventional phenolic epoxy resin is relatively low. In order to increase the room temperature viscosity of the prepreg resin composition, the present application further adds 20 to 75 parts of bisphenol A type solid epoxy resin to the composition for viscosity enhancement. However, the viscosity thixotropy of bisphenol A type solid epoxy resin is relatively poor. Although it can increase the room temperature viscosity of the prepreg resin, the viscosity of the resin system is still relatively high (above 5000cps) at an impregnation temperature of 60 to 80°C, which is difficult to reduce, which will result in a poor impregnation effect of the prepreg resin. The above-mentioned core-shell nanoparticles have more excellent viscosity thixotropy, with a higher viscosity at low temperatures, and their viscosity decreases significantly as the temperature rises. Thereby, the prepreg resin can be further endowed with good temperature thixotropy, with ultra-high viscosity at room temperature, no glue flow or overflow, and can quickly become thinner when heated, thereby making the resin and carbon fiber have good wettability.
[0030] It should also be noted that if the amount of the above components is not within the above range, the prepreg resin cannot simultaneously take into account a lower curing temperature, a longer storage period, better toughness and good viscosity thixotropy.
[0031] In order to further balance the above excellent properties of the prepreg tape resin. In a preferred embodiment, the prepreg tape resin composition includes: 55-80 parts of bisphenol A type liquid epoxy resin, 40-55 parts of bisphenol A type solid epoxy resin, 15-40 parts of novolac epoxy resin, 15-20 parts of core-shell nanoparticles, 4-6 parts of latent curing agent, and 1-3 parts of accelerator.
[0032] In a preferred embodiment, the bisphenol A type liquid epoxy resin is a liquid bisphenol A diglycidyl ether with a number average molecular weight of less than 800. Based on this, the prepreg tape resin has excellent corrosion resistance and chemical resistance, good heat stability, and good environmental protection. Preferably, the bisphenol A type liquid epoxy resin is selected from one or more of E-56D (for example, available from Nantong Xingchen manufacturer), E-54 (for example, available from Nanya manufacturer in Taiwan, China), E-52D (for example, available from Nantong Xingchen manufacturer), E-51 (for example, available from Nantong Xingchen manufacturer), E-44B (for example, available from Nantong Xingchen manufacturer), E-44 (for example, available from Nantong Xingchen manufacturer), E-42 (for example, available from Nantong Xingchen manufacturer), and E-39D (for example, available from Nantong Xingchen manufacturer).
[0033] In a preferred embodiment, the bisphenol A type solid epoxy resin is a solid bisphenol A diglycidyl ether with a number average molecular weight ≥ 800. Based on this, the prepreg tape resin has a better room temperature tackifying effect and better mechanical properties. Preferably, the bisphenol A type solid epoxy resin is selected from one or more of E-21 (for example, available from Nantong Xingchen manufacturer), E-20 (for example, available from Nantong Xingchen manufacturer), E-14 (for example, available from Nantong Xingchen manufacturer), E-13 (for example, available from Nantong Xingchen manufacturer), CYD-011 (for example, available from Baling Petrochemical), CYD-012 (for example, available from Baling Petrochemical), and CYD-001 (for example, available from Baling Petrochemical).
[0034] In some optional embodiments, the novolac epoxy resin is selected from one or more of linear phenol formaldehyde glycidyl ether, o-cresol formaldehyde glycidyl ether, and resorcinol formaldehyde glycidyl ether. In order to further balance the above-mentioned excellent properties of the prepreg tape resin, preferably, linear phenol formaldehyde glycidyl ether is selected from one or more of F-51 (for example, available from Baling Petrochemical Factory), F-48 (for example, available from Baling Petrochemical Factory), F-44 (for example, available from Baling Petrochemical) or NPPN-638S (for example, available from Nanya Group); o-cresol formaldehyde glycidyl ether is selected from one or more of JF-45 (for example, available from Baling Petrochemical Factory), JF-46 (for example, available from Baling Petrochemical Factory), JF-43 (for example, available from Wuxi Resin Factory) or EDCN-220 (for example, available from Baling Petrochemical); resorcinol formaldehyde glycidyl ether is selected from one or more of F-76 (for example, available from Tianjin Synthetic Materials Research Institute) and / or CYDPG-694 (for example, available from Baling Petrochemical).
[0035] In order to further balance the comprehensive performance of the prepreg, in a preferred embodiment, the particle size of the core-shell nanoparticles is 50 to 200 nm. In the core-shell nanoparticles, the rubber is selected from one or more of silicone rubber, styrene-butadiene rubber or polybutadiene rubber. Compared with other rubbers, the above rubber has a certain flexibility and can have good compatibility and reactivity with the hard plastic of the shell. The hard plastic is selected from one or more of polymethyl methacrylate, polybutyl methacrylate or polystyrene. Further preferably, the core-shell nanoparticles are selected from one or more of MX-154 (for example, purchased from KANEKA, Japan), MX-153 (for example, purchased from KANEKA, Japan), MX-960 (for example, purchased from KANEKA, Japan), XA-492 (for example, purchased from Jiadida) or XA-542 (for example, purchased from Jiadida).
[0036] In order to further increase the shelf life of the prepreg resin, in a preferred embodiment, the latent curing agent is selected from one or more of cyanamide compounds, imidazole derivatives or boron trifluoride complexes. Preferably, the cyanamide compound is selected from dicyandiamide and / or diallyl melamine; the imidazole derivative is selected from 2MZ-AZINE (for example, available from Evonik Chemicals) and / or 2E4MZ-AZINE (for example, available from Evonik Chemicals); and the boron trifluoride complex is selected from BF3·MEA (for example, available from Evonik Chemicals).
[0037] In order to further balance the storage period and curing temperature of the prepreg resin, in a preferred embodiment, the accelerator is selected from one or more of acetylacetonate metal salt accelerator, modified imidazole accelerator, modified urea accelerator, and modified tertiary amine accelerator. Preferably, the acetylacetonate metal salt accelerator is selected from ferric acetylacetonate and / or chromium acetylacetonate; the modified imidazole accelerator is selected from 2,4-EMI (for example, available from Evonik Chemicals) and / or 2MZ-ZN (for example, available from Evonik Chemicals); the modified urea accelerator is selected from DCMU (for example, available from Evonik Chemicals) and / or UR400 (for example, available from Azken, Germany); the modified tertiary amine accelerator is selected from one or more of MY-24 (for example, available from Ajinomoto, Japan), DMP-30 (for example, available from Evonik Chemicals) or TAP (for example, available from Evonik Chemicals).
[0038] In order to further balance the above excellent properties of the prepreg resin, in a preferred embodiment, the prepreg resin composition includes, by weight: E-54: 75-80 parts; CYD-011: 45-50 parts; JF-46: 15-20 parts; SBR resin core-shell nanoparticles: 15-20 parts; BF3·MEA: 4-5 parts; 2,4-EMI: 0.5-1 part; MY-24: 0.5-1 part; or the prepreg resin composition includes: E-44: 55-60 parts; CYD-001: 40 ~45 parts; F-48: 35~40 parts; PBd resin core-shell nanoparticles: 15~20 parts; dicyandiamide: 5~6 parts; MY-24: 1~2 parts; DMP-30: 0.1~0.5 parts; or, the prepreg resin composition includes: E-51: 65~70 parts; CYD-012: 50~55 parts; F-51: 30~35 parts; PBd resin core-shell nanoparticles: 15~20 parts; diallyl melamine: 5~6 parts; MY-24: 1~1.5 parts; 2,4-EMI: 1~1.5 parts. At the same time, the use of modified imidazoles, modified ureas, modified tertiary amines and other accelerators, the complementary performance of the compound of multiple modified accelerators reduces the total amount of accelerators added, improves the accelerator efficiency, and avoids the problem of shortening the storage period due to the addition of a single accelerator. The prepreg resin can be stored at room temperature for 20 to 50 days and can be stored in a -18°C cold storage for at least 6 months.
[0039] In a preferred embodiment, the prepreg resin composition can be prepared by the following method: bisphenol A liquid epoxy resin, bisphenol A solid epoxy resin, phenolic epoxy resin, core-shell nanoparticles are mixed at a stirring speed of 100 to 500 rpm and a temperature of 90 to 150° C. for 2 to 8 hours to obtain a mixed solution 1. The mixed solution 1 is cooled to 50 to 80° C., and then a latent curing agent and an accelerator are added to the mixed solution 1 in sequence, and mixed at a stirring speed of 100 to 300 rpm and a temperature of 20 to 80° C. for 1 to 5 hours to obtain a mixed solution 2. The mixed solution 2 is ground 1 to 3 times with a three-roll grinder to completely mix it to obtain a mixed solution 3. Then, the mixed solution 3 is packaged using a tray, cooled to room temperature, and refrigerated in a cold storage (-10 to -30° C.) to obtain a prepreg resin composition.
[0040] The present application also provides a carbon fiber prepreg material, which includes carbon fiber and the above-mentioned prepreg tape resin composition impregnated in the carbon fiber. Based on the above reasons, the prepreg tape resin of the present application can take into account lower curing temperature, longer storage period, better toughness and good viscosity thixotropy at the same time. Such prepreg tape resin has better impregnation effect.
[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0042] Example 1
[0043] In terms of weight, the prepreg resin composition includes: E-54 (purchased from Nan Ya manufacturer in Taiwan, China): 80 parts; CYD-011 (purchased from Baling Petrochemical): 50 parts; JF-46 (purchased from Baling Petrochemical): 20 parts; core-shell nanoparticles XA-542 (purchased from Jiadida manufacturer): 20 parts; BF3·MEA (purchased from Evonik Chemical manufacturer): 5 parts; 2,4-EMI (purchased from Evonik Chemical manufacturer): 1 part; MY-24 (purchased from Ajinomoto manufacturer in Japan): 1 part.
[0044] (1) Add 80 parts of E-54, 50 parts of CYD-011, 20 parts of JF-46, and 20 parts of XA-542 into a mixing kettle and mix them at a stirring speed of 400 rpm, a temperature of 100°C, and a stirring time of 5 hours.
[0045] (2) After stirring, the mixed solution was cooled to 40°C, and 5 parts of BF3·MEA, 1 part of 2,4-EMI, and 1 part of MY-24 were added in sequence, and then continued to stir in the mixing kettle at a stirring speed of 200 rpm, a stirring time of 1 hour, and a stirring temperature of 60°C.
[0046] (3) Then, the mixture was ground twice using a three-roll mill until it was completely uniform.
[0047] (4) Cool the thoroughly mixed glue solution to room temperature, then seal and store at -18°C.
[0048] The prepreg resin composition has a long storage period, and after being stored at room temperature for 30 days, the DSC curing heat release is reduced by only one tenth.
[0049] The prepreg tape resin composition can be completely cured by pre-curing at 90° C. for 1 hour and curing at 115° C. for 3 hours without affecting the performance of the plastic liner.
[0050] The prepreg resin composition has good viscosity thixotropy. Figure 1 The viscosity-temperature curve of the prepreg tape resin composition is shown. The viscosity at 30°C is 140,000 to 250,000 cps, which can ensure that the prepreg tape does not flow or overflow after impregnation; at a temperature of 60 to 80°C, the viscosity drops rapidly to 500 to 1500 cps, which can make the prepreg tape have a good impregnation effect.
[0051] The notched impact strength of the prepreg resin is 3.5 kJ / m 2 , good toughness.
[0052] Example 2
[0053] In terms of weight, the prepreg resin composition includes: E-44 (purchased from Nantong Xingchen manufacturer): 60 parts; CYD-001 (purchased from Baling Petrochemical manufacturer): 45 parts; F-48 (purchased from Baling Petrochemical manufacturer): 40 parts; core-shell nanoparticles MX-154 (purchased from Japan's KANEKA): 20 parts; micro-powder grade dicyandiamide (commercially available model DDA-5): 6 parts; MY-24 (purchased from Japan's Ajinomoto manufacturer): 2 parts; DMP-30 (purchased from Evonik Chemical manufacturer): 0.5 parts.
[0054] (1) Add 60 parts of E-44, 45 parts of CYD-001, 40 parts of F-48, and 20 parts of MX-154 into a mixing kettle and mix them at a stirring speed of 500 rpm, a temperature of 120°C, and a stirring time of 1.5 hours.
[0055] (2) After stirring, the mixture was cooled to 70°C, and 6 parts of micronized dicyandiamide, 2 parts of MY-24, and 0.5 parts of DMP-30 were added in sequence, and then continued to stir in the mixing kettle at a stirring speed of 300 rpm, a stirring time of 1 hour, and a stirring temperature of 50°C.
[0056] (3) Then, the mixture was ground twice using a three-roll mill until it was completely uniform.
[0057] (4) Cool the thoroughly mixed glue solution to room temperature, then seal and store at -18°C.
[0058] The prepreg resin composition has a long storage period, and after being stored at room temperature for 30 days, the DSC curing heat release is reduced by only one tenth.
[0059] The prepreg tape resin composition can be completely cured by pre-curing at 90° C. for 1.5 hours and curing at 120° C. for 3 hours without affecting the performance of the plastic liner.
[0060] The prepreg tape resin composition has good viscosity thixotropy. The viscosity at 30°C is 100,000 to 350,000 cps, which can ensure that the prepreg tape does not flow or overflow after impregnation; at a temperature of 60 to 80°C, the viscosity rapidly drops to 500 to 2000 cps, which can make the prepreg tape have a good impregnation effect.
[0061] The notched impact strength of the prepreg resin is 3.5 kJ / m 2 , good toughness.
[0062] Example 3
[0063] In terms of weight, the prepreg resin composition includes: E-51 (purchased from Nantong Xingchen manufacturer): 65 parts; CYD-012 (purchased from Baling Petrochemical manufacturer): 50 parts; F-51 (purchased from Baling Petrochemical manufacturer): 30 parts; MX-154 (purchased from Japan's KANEKA): 20 parts; diallyl melamine: 5 parts; MY-24 (purchased from Japan's Ajinomoto manufacturer): 1 part; 2,4-EMI (purchased from Evonik Chemical manufacturer): 1 part.
[0064] (1) Add 65 parts of E-51, 50 parts of CYD-012, 30 parts of F-51, and 20 parts of MX-154 into a mixing kettle and mix them at a stirring speed of 300 rpm, a temperature of 110°C, and a stirring time of 2 hours.
[0065] (2) After stirring, the mixture was cooled to 80°C, and 5 parts of diallyl melamine, 1 part of MY-24, and 1 part of 2,4-EMI were added in sequence, and then continued to stir in the mixing kettle at a stirring speed of 150 rpm, a stirring time of 1 hour, and a stirring temperature of 70°C.
[0066] (3) Then, the mixture was ground twice using a three-roll mill until it was completely uniform.
[0067] (4) Cool the thoroughly mixed glue solution to room temperature, then seal and store at -18°C.
[0068] The prepreg resin composition has a long storage period, and after being stored at room temperature for 30 days, the DSC curing heat release is reduced by only one tenth.
[0069] The prepreg tape resin composition can be completely cured by pre-curing at 90° C. for 1 hour and curing at 120° C. for 3 hours without affecting the performance of the plastic liner.
[0070] The prepreg tape resin composition has good viscosity thixotropy. The viscosity at 30°C is 100,000 to 350,000 cps, which can ensure that the prepreg tape does not flow or overflow after impregnation; at a temperature of 60 to 80°C, the viscosity drops rapidly to 800 to 1500 cps, which can make the prepreg tape have a good impregnation effect.
[0071] The notched impact strength of the prepreg resin is 3.8 kJ / m 2 , good toughness.
[0072] Example 4
[0073] The only difference from Example 1 is that, by weight, the prepreg resin composition includes: E-54: 25 parts; CYD-011: 20 parts; JF-46: 15 parts; core-shell nanoparticles XA-542: 5 parts; BF3·MEA: 3 parts; 2,4-EMI: 0.25 parts; MY-24: 0.25 parts.
[0074] The prepreg resin composition has a long storage period, and after being stored at room temperature for 30 days, the DSC curing heat release is reduced by only one tenth.
[0075] The prepreg tape resin composition can be completely cured by pre-curing at 90° C. for 1 hour and curing at 120° C. for 3 hours without affecting the performance of the plastic liner.
[0076] The prepreg tape resin composition has good viscosity thixotropy. The viscosity at 30°C is 100,000 to 300,000 cps, which can ensure that the prepreg tape does not flow or overflow after impregnation; at a temperature of 60 to 80°C, the viscosity drops rapidly to 800 to 2000 cps, which can make the prepreg tape have a good impregnation effect.
[0077] The notched impact strength of the prepreg resin is 3.8 kJ / m 2 , good toughness.
[0078] Example 5
[0079] The prepreg tape resin composition comprises, by weight: 80 parts of CYD-128; 50 parts of E-03; 20 parts of FM-15; 20 parts of German Wacker P52; 5 parts of dicyandiamide; and 1 part of DMP-30.
[0080] The prepreg resin composition has a long storage period, and after being stored at room temperature for 30 days, the DSC curing heat release is reduced by only one eighth.
[0081] The prepreg tape resin composition can be completely cured by pre-curing at 100° C. for 2 hours and curing at 120° C. for 4 hours without affecting the performance of the plastic liner.
[0082] The prepreg tape resin composition has good viscosity thixotropy. The viscosity at 30°C is 200,000 to 400,000 cps, which can ensure that the prepreg tape does not flow or overflow after impregnation. At a temperature of 60 to 80°C, the viscosity drops rapidly to 4,000 to 5,000 cps, and the prepreg tape impregnation effect is average.
[0083] The notched impact strength of the prepreg resin is 3.1 kJ / m 2 , good toughness.
[0084] Comparative Example 1
[0085] The only difference from Example 2 is that, by weight, the prepreg resin composition includes: E-44: 18 parts; CYD-001: 9 parts; F-48: 15 parts; micronized dicyandiamide: 7 parts; 2,4-toluene dimethyl urea accelerator (isomer grade, American CVC manufacturer, U24M brand): 5 parts.
[0086] The prepreg resin composition has a long storage period. After 30 days of storage at room temperature, the DSC curing heat release decreased by one-half. The decrease in heat release indicates that the resin has reacted during storage at room temperature, and the reaction degree is high, indicating poor storage performance. The more the heat release decreases, the worse the storage performance.
[0087] The prepreg tape resin composition is pre-cured at 100° C. for 2 hours and cured at 150° C. for 5 hours before being completely cured, and the performance of the plastic liner is slightly damaged.
[0088] The prepreg tape resin composition has good viscosity thixotropy. The viscosity at 30°C is 100,000 to 300,000 cps, which can ensure that the prepreg tape does not flow or overflow after impregnation. At a temperature of 60 to 80°C, the viscosity drops to 10,000 to 12,000 cps. If the viscosity is too high, the impregnation effect of the prepreg tape is poor.
[0089] The notched impact strength of the prepreg resin is 2.0 kJ / m 2 , poor toughness.
[0090] Through Examples 1-5 and Comparative Example 1, it can be found that, by weight, when the prepreg resin composition includes 25-80 parts of bisphenol A liquid epoxy resin, 20-75 parts of bisphenol A solid epoxy resin, 15-50 parts of phenolic epoxy resin, 5-20 parts of core-shell nanoparticles, 3-8 parts of latent curing agent and 0.5-5 parts of accelerator, the prepreg resin can simultaneously take into account lower curing temperature, longer storage period, better toughness and good viscosity thixotropy. When the prepreg resin composition does not add core-shell nanoparticles, and the amount of each component is not within the above range, the product needs to be cured at a higher curing temperature, which will cause slight damage to the performance of the plastic liner; its storage period will also be shortened, and it cannot meet the long-term storage requirements; its toughness will also be reduced; in particular, the product viscosity thixotropy is poor, and it cannot meet the prepreg requirements during application.
[0091] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A prepreg resin composition, characterized in that The prepreg tape resin composition comprises, by weight: 25 to 80 parts of bisphenol A type liquid epoxy resin, 20 to 75 parts of bisphenol A type solid epoxy resin, 15 to 50 parts of novolac epoxy resin, 5 to 20 parts of core-shell nanoparticles, 3 to 8 parts of latent curing agent, and 0.5 to 5 parts of accelerator; The core of the core-shell nanoparticles is rubber, and the shell is hard plastic.
2. The prepreg resin composition according to claim 1, characterized in that In parts by weight, the prepreg resin composition comprises: 55 to 80 parts of the bisphenol A liquid epoxy resin, 40 to 55 parts of the bisphenol A solid epoxy resin, 15 to 40 parts of the phenolic epoxy resin, 15 to 20 parts of the core-shell nanoparticles, 4 to 6 parts of the latent curing agent, and 1 to 3 parts of the accelerator.
3. The prepreg resin composition according to claim 1, characterized in that The particle size of the core-shell nanoparticles is 50 to 200 nm; Preferably, in the core-shell nanoparticles, the hard plastic is selected from one or more of polymethyl methacrylate, polybutyl methacrylate or polystyrene; Preferably, in the core-shell nanoparticles, the rubber is selected from one or more of silicone rubber, styrene-butadiene rubber or polybutadiene rubber; Further preferably, the core-shell nanoparticles are selected from one or more of MX-154, MX-153, MX-960, XA-492 or XA-542.
4. The prepreg resin composition according to any one of claims 1 to 3, characterized in that The bisphenol A type liquid epoxy resin is selected from one or more of E-56D, E-54, E-52D, E-51, E-44B, E-44, E-42 or E-39D.
5. The prepreg resin composition according to any one of claims 1 to 3, characterized in that The bisphenol A type solid epoxy resin is selected from one or more of E-21, E-20, E-14, E-13, CYD-011, CYD-012 or CYD-001.
6. The prepreg resin composition according to any one of claims 1 to 3, characterized in that The phenolic epoxy resin is selected from one or more of linear phenol formaldehyde glycidyl ether, o-cresol formaldehyde glycidyl ether or resorcinol formaldehyde glycidyl ether; Further preferably, the linear phenol formaldehyde glycidyl ether is selected from one or more of F-51, F-48, F-44 or NPPN-638S; Further preferably, the o-cresol formaldehyde glycidyl ether is selected from one or more of JF-45, JF-46, JF-43 or EDCN-220; Further preferably, the resorcinol formaldehyde glycidyl ether is selected from F-76 and / or CYDPG-694.
7. The prepreg resin composition according to any one of claims 1 to 3, characterized in that The latent curing agent is selected from one or more of cyanamide compounds, imidazole derivatives or boron trifluoride complexes; Preferably, the cyanamide compound is selected from dicyandiamide and / or diallyl melamine; Preferably, the imidazole derivative is selected from 2MZ-AZINE and / or 2E4MZ-AZINE; Preferably, the boron trifluoride complex is selected from BF3·MEA.
8. The prepreg resin composition according to any one of claims 1 to 3, characterized in that The accelerator is selected from one or more of acetylacetone metal salt accelerators, modified imidazole accelerators, modified urea accelerators, and modified tertiary amine accelerators; Preferably, the acetylacetonate metal salt promoter is selected from ferric acetylacetonate and / or chromium acetylacetonate; Preferably, the modified imidazole accelerator is selected from 2,4-EMI and / or 2MZ-ZN; Preferably, the modified urea accelerator is selected from DCMU and / or UR400; Preferably, the modified tertiary amines are selected from one or more of MY-24, DMP-30 or TAP.
9. The prepreg resin composition according to claim 1, characterized in that: In parts by weight, the prepreg resin composition comprises: E-54: 75-80 parts; CYD-011: 45-50 parts; JF-46: 15-20 parts; XA-542: 15-20 parts; BF3·MEA: 4-5 parts; 2,4-EMI: 0.5-1 parts; MY-24: 0.5-1 parts; or, The prepreg resin composition comprises: E-44: 55-60 parts; CYD-001: 40-45 parts; F-48: 35-40 parts; MX-154: 15-20 parts; dicyandiamide: 5-6 parts; MY-24: 1-2 parts; DMP-30: 0.1-0.5 parts; or, The prepreg resin composition comprises: E-51: 65-70 parts; CYD-012: 50-55 parts; F-51: 30-35 parts; XA-542: 15-20 parts; diallyl melamine: 5-6 parts; MY-24: 1-1.5 parts; 2,4-EMI: 1-1.5 parts.
10. A carbon fiber prepreg material, characterized in that: The carbon fiber prepreg comprises carbon fibers and the prepreg resin composition according to any one of claims 1 to 9 impregnated in the carbon fibers.
Citation Information
Cited By
Composite ultrathin bonding sheet for multi-layer lamination of high-frequency copper-clad plate and preparation method of composite ultrathin bonding sheet
CN119979092A
